Understanding the shift to compulsion in addiction: insights from personality traits, social factors, and neurobiology - Su, Haodong; Ye, Tongtong; Cao, Songyan; Hu, Chunyan (Frontiers in Psychology, 2024)
Compulsion stands as a central symptom of drug addiction; however, only a small fraction of individuals who use drugs exhibit compulsive characteristics. Differences observed in Sign-trackers (ST) and Goal-trackers (GT) during Pavlovian conditioning may shed light on individual variances in drug addiction. Here, we focus on the behavioral attributes, formation processes, and neural mechanisms underlying ST and how they drive addiction toward compulsivity in humans. We will explore addiction from three interconnected levels: individual personality traits, social factors, and neurobiology. Furthermore, we distinguish between the processes of sensitization and habituation within ST. These nuanced distinctions across various aspects of addiction will contribute to our understanding of the addiction development process and the formulation of targeted preventive strategies.